Pengaruh Indeks Pembangunan Manusia (Ipm) Dan Pengangguran Terhadap Kemiskinan Di Kabupaten Bone Pada Tahun 2011–2021 - Sari, Susindah; Patimbangi, Andi (Islamic Banking and Finance, 2023)
The purpose of this study was to find out how much influence the human development index (HDI) and unemployment simultaneously have on poverty in Bone Regency in 2011-2021. The research method used is expo facto. The results of this study describe the description of the data, the Development of the Human Development Index (IPM) Unemployment and Poverty in Bone Regency in 2011-2021. This study uses several tests, namely: Multiple linear regression test, Normality test, Heteroscedasticity test, Multicollinearity test, Autocorrelation test. The results of hypothesis testing: t test and f test and the last one is the coefficient of determination.